A252 METASTASIS TO THE PANCREAS: THE EXPERIENCE OF A HIGH VOLUME HEPATO- PANCREATIC BILLIARY CENTRE. (1st March 2018) - Taylor, S A; Chiu, K; Byrne, M; Schaeffer, D F; Donnellan, F
Abstract: Background: Pancreatic metastases (PM) from non-pancreatic primaries are rare, but should be considered in patients with a prior history of malignancy. PM's represent less than 2% of all pancreatic neoplasms. Studies have not adequately evaluated the ideal oncologic and combined surgical approach for pancreatic metastasis. Aims: The aim of this study was to investigate the clinico-pathological presentation of patients with secondary tumors of the pancreas and surgical management. Methods: We retrospectively identified patients from a high volume hepato-pancreato-billiary database in Canada dating from January 1989- September 2015. Medical records were retrospectively analyzed for clinical presentation, pathologic details, time period between the diagnosis of the primary tumor to metastasis or disease free interval (DFI), tumor size, focality and surgical resectability. Results: We identified 103 patients (median age 53.5) with disease metastatic to the pancreas for which cytologic material was available via endoscopic ultrasound (EUS) fine needle aspiration (n=49, 47.6%), EUS core biopsy (n=14, 13.6%) or upfront definitive surgical resection (n=38 36.7%). Renal carcinoma was the most common tumor to metastasize to the pancreas (52%), followed by lung carcinoma (10%), colonic adenocarcinoma (10%), melanoma (6%) and breast (6%) followed by 10 other primary tumors. The median DFI was 6.8 years (inter-quartile range 1.23–12.78) between diagnoses of primary malignancy to metastasis. There was a significant difference in DFI for RCC (median 9.7 years, p <0.05) and 4.5 years compared to all other pathologies. 38 (36.7%) patients with a median age of 58.5 (range 33–79) were identified to have pancreatic metastasis amenable to surgical resection. The average size of the metastatic lesions in greatest dimension was 2.6 cm (range: 1.2-7cm) and the majority were a single focus. Open surgical distal pancreatectomy with or without splenectomy was the most common operation (n=10, 26%) followed by pancreaticoduodenectomy (n=9, 23%) and there were no postoperative deaths. The median survival of resected patients captured to follow-up via electronic medical record (n=18) was 31 months (range: 16–87 months). Conclusions: The most common metastatic tumor to the pancreas was identified as RCC, which is in accordance with the literature. Tissue acquisition via EUS is an increasingly useful modality for guiding precision to surgical resection of pancreatic tumors with the ultimate goal of rendering a patient disease free and reducing perioperative morbidity. Funding Agencies: CAG